An Empirical Study of Compatibility of Advertising Channels and Product Categories - Saxena, Karunesh; Paliwal, Pramod; Tripathi, Pooja (Indian Journal of Marketing, 2007)
Due to globalization the competition pressure increases many fold. Earlier the bad company were not able to survive, now even the good companies are finding it difficult to face the onslaught of competition consequently the business organisation are striving to economize all areas of their operations. In order to increase their market share the marketers are trying to achieve maximum utilization of their ads spend. In this paper the compatibility of types of TV Channels with appropriate product categories had been empirically tested. The paper concludes with useful suggestion given to the marketing professional to achieve the above stated objectives.